Non-contrast-enhanced MR portography and hepatic venography with time-spatial labeling inversion pulses: comparison at 1.5 Tesla and 3 Tesla. (18th May 2015) - Ohno, Tsuyoshi; Isoda, Hiroyoshi; Furuta, Akihiro; Togashi, Kaori
Background: A 3 Tesla (3 T) magnetic resonance (MR) scanner is a promising tool for upper abdominal MR angiography. However, there is no report focused on the image quality of non-contrast-enhanced MR portography and hepatic venography at 3 T. Purpose: To compare and evaluate images of non-contrast-enhanced MR portography and hepatic venography with time-spatial labeling inversion pulses (Time-SLIP) at 1.5 Tesla (1.5 T) and 3 T. Material and Methods: Twenty-five healthy volunteers were examined using respiratory-triggered three-dimensional balanced steady-state free-precession (bSSFP) with Time-SLIP. For portography, we used one tagging pulse (selective inversion recovery) and one non-selective inversion recovery pulse; for venography, two tagging pulses were used. The relative signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR) were quantified, and the quality of visualization was evaluated. Results: The CNRs of the main portal vein, right portal vein, and left portal vein at 3 T were better than at 1.5 T. The image quality scores for the portal branches of segment 4, 5, and 8 were significantly higher at 3 T than at 1.5 T. The CNR of the right hepatic vein (RHV) at 3 T was significantly lower than at 1.5 T. The image quality scores of RHV and the middle hepatic vein were higher at 1.5 T than at 3 T. For RHV visualization, the difference was statistically significant. Conclusion: Non-contrast-enhanced MR portography with Time-SLIP at 3 T significantly improved visualization of the peripheral branch in healthy volunteers compared with1.5 T. Non-contrast-enhanced MR hepatic venography at 1.5 T was better than at 3 T.